Extent of Differentiated Instruction Implementation Among Teachers in Public Elementary Schools of Santa Fe District, Nueva Vizcaya - Patil, Niki (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study sought to understand the extent to which differentiated instruction is implemented by teachers in public elementary schools within the Santa Fe District, Nueva Vizcaya, during the School Year 2025–2026. Specifically, it explored the respondents’ profiles, their perceptions of differentiated instruction, the instructional strategies they employed, the learning settings, the areas of differentiated instruction, the challenges they encountered, and the relationship between respondents’ profile variables and the implementation of differentiated instruction. This study employed a descriptive-correlational research design and utilized a researcher-made questionnaire as the primary data-gathering instrument. A complete enumeration was conducted involving twenty-eight (28) Grade 1 and Grade 2 teachers from public elementary schools in the district. Frequency counts, percentages, weighted means, standard deviations, and Pearson’s r correlation analysis were used to analyze the gathered data. The findings indicate that teachers hold positive perceptions of differentiated instruction and frequently employ varied instructional strategies and learning settings in their classrooms. Assessment, instructional strategies, and learner-centered activities were identified as important components for addressing diverse learner needs. Although teachers faced challenges such as limited instructional resources and classroom diversity, they were manageable. Furthermore, educational attainment, performance rating, present position, and training attended showed significant relationships with the implementation of differentiated instruction. The study concluded that differentiated instruction is an effective teaching approach that promotes learner engagement, participation, and academic performance among elementary pupils in diverse classroom settings.
Keywords: Differentiated Instruction; Instructional Strategies; Learning Settings; Elementary Teachers; Learner-Centered Education